EFEKTIFITAS METODE VAKT UNTUK MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN BAGI ANAK KESULITAN BELAJAR - Syafrina Maulana, Ganda Sumekar, Mega Iswari (Universitas Negeri Padang, 2013)
Research early from problems which is writer find in second grade at Min Koto Luar Padang. Child write the letter with imprecise form, size measure and not consistence distance of letter, the article fluctuate at paper mark with lines, and add, lessening, changing and also invert letter at a word. So we need a special method to solve this problems, one of them is method of VAKT. This research use experiment type with single subject and A-B-A design. Acquirement of data analysed to use analyse visual data technique. Result of data analysis percentage of overlap equal to 0% and 22%. And it’s mean Ha accepted. VAKT method effective to increase write ability to Learning Disabilities Children in second grade MIN Koto Luar Padang. So writer suggest to teacher to use VAKT method in lesson process specially write lesson.